2010
DOI: 10.1371/journal.pone.0008781
|View full text |Cite
|
Sign up to set email alerts
|

Postcoital Bioavailability and Antiviral Activity of 0.5% PRO 2000 Gel: Implications for Future Microbicide Clinical Trials

Abstract: BackgroundThe pharmacokinetics and pharmacodynamics of vaginal microbicides are typically assessed among sexually abstinent women. However, the physical act of sex may modulate gel distribution, and preclinical studies demonstrate seminal plasma interferes with the antiviral activity of several microbicides. This study compared the biological activity and concentration of PRO 2000 in cervicovaginal lavage (CVL) collected in the absence or following coitus.MethodsCVL samples were collected from ten heterosexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 22 publications
9
63
0
Order By: Relevance
“…CVL from participants exposed to placebo vaginal rings inhibited HIV-infection by a mean of 18% when used neat, but the activity was lost when samples were diluted 1:10 ( Figure 3). This low level of activity was attributed to some innate inhibition in vaginal lavage fluid, an effect that has been documented previously [22,27,28]. In contrast, samples from participants treated with rings containing dapivirine inhibited HIVinfection by a mean of 89% when used neat, and retained 71% inhibitory activity when diluted 10-fold (Figure 3).…”
Section: Pharmacodynamicsmentioning
confidence: 58%
See 1 more Smart Citation
“…CVL from participants exposed to placebo vaginal rings inhibited HIV-infection by a mean of 18% when used neat, but the activity was lost when samples were diluted 1:10 ( Figure 3). This low level of activity was attributed to some innate inhibition in vaginal lavage fluid, an effect that has been documented previously [22,27,28]. In contrast, samples from participants treated with rings containing dapivirine inhibited HIVinfection by a mean of 89% when used neat, and retained 71% inhibitory activity when diluted 10-fold (Figure 3).…”
Section: Pharmacodynamicsmentioning
confidence: 58%
“…A CVL was performed by rinsing the cervical os and posterior vaginal wall with 10 mL of sterile saline [22,23]. The fluid was collected in a labeled 15 mL conical polypropylene tube.…”
Section: Pharmacodynamic Assessment Of Anti-hiv Activity Of Dapivirinmentioning
confidence: 99%
“…The differences in results obtained between SPL7013 and G2-S16 dendrimers could be because SPL7013 is a PLLdendrimer with 32 anionic naphthalene sulfonate groups in the periphery, and it has been shown that semen components or the alkaline pH of semen decreases the anti-HIV activity of polyanions by neutralizing their negative charge 24,[30][31][32][33] or by competitive binding to the viral envelope. 34 These data provide conceivable explanations as to why semen abrogates the antiviral activity of polyanions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that semen may inhibit UC781 antiviral activity in vivo as has been suggested for other microbicide candidates, although previous in vitro studies indicate that UC781 is unaffected by seminal plasma (15,18). Additionally, UC781 bioavailability may be reduced during coitus as recently reported by Keller et al for PRO2000, potentially rendering UC781 microbicide gel less effective against HIV infection (16). Through the use of multiple tests incorporating seminal plasma, coitus, and ex vivo assays, future safety and preclinical trials will be able to generate important results regarding the potential efficacy of microbicide candidates prior to extensive clinical efficacy trials.…”
Section: Distribution Of Uc781 Levels In Cervicovaginal Lavagesmentioning
confidence: 93%
“…The preclinical testing outcomes for all of these products suggested that they might significantly reduce sexual transmission of HIV when used appropriately in a clinical trial. However, a recent report using ex vivo testing of PRO2000 claimed that this product may lose some of its anti-infective activity after vaginal application and sexual intercourse (16). Except for PRO2000, it is not known whether exposure of microbicide gels to female genital secretions in vivo lowers their anti-HIV activity and may have contributed to the disappointing outcomes in some clinical efficacy trials.…”
mentioning
confidence: 99%